Application of non-canonical crosslinking amino acids to study protein–protein interactions in live cells. (October 2018) - Coin, Irene
Abstract : The genetic incorporation of non-canonical amino acids (ncAAs) equipped with photo-crosslinking and chemical crosslinking moieties has found broad application in the study of protein–protein interactions from a unique perspective in live cells. We highlight here applications of photo-activatable ncAAs to map protein interaction surfaces and to capture protein–protein interactions, and we describe recent efforts to efficiently couple photo-crosslinking with mass spectrometric analysis. In addition, we describe recent advances in the development and application of ncAAs for chemical crosslinking, including protein stapling, photo-control of protein conformation, two-dimensional crosslinking, and stabilization of transient and low-affinity protein–protein interactions. We expect that the field will keep growing in the near future and enable the tackling of ambitious biological questions.